2015
DOI: 10.1371/journal.pone.0135318
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Genetic Polymorphisms of Osteopontin Promoter and Susceptibility to Cancer in Chinese Population: A Meta-Analysis

Abstract: Background and AimSeveral studies have been conducted to examine the associations between osteopontin (OPN) promoter gene SPP1 polymorphisms with human cancers in Chinese population, but the results remain inconsistent. The aim of this meta-analysis is to clarify the associations between SPP1 polymorphisms and cancer susceptibility.MethodsAll eligible case-control studies published up to March 2015 were identified by searching PubMed, Web of Science, Embase, and Cochrane Library without language restrictions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…All three SPP1 promoter SNPs at−66,−156, and−443 have been surveyed simultaneously in several diseases, including ischemic stroke ( 10 ), glioma ( 15 ), osteoarthritis ( 12 ), cervical spondylotic myelopathy ( 13 ), and a variety of cancers ( 11 , 14 ). It had also been proved that the haplotype−443T/-156GG/-66G appear to significantly lower promoter activity in comparison to the other five haplotypes ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…All three SPP1 promoter SNPs at−66,−156, and−443 have been surveyed simultaneously in several diseases, including ischemic stroke ( 10 ), glioma ( 15 ), osteoarthritis ( 12 ), cervical spondylotic myelopathy ( 13 ), and a variety of cancers ( 11 , 14 ). It had also been proved that the haplotype−443T/-156GG/-66G appear to significantly lower promoter activity in comparison to the other five haplotypes ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the case of other solid tumors, such as, e.g., glioma or oral, nasopharyngeal, hepatocellular, and breast cancers, variant C was protective in terms of cancer risk or prognosis [36,[46][47][48][49]. The results of a meta-analysis based on 11 studies in the Chinese population, including the NSCLC study, suggested in turn that rs11730582 had no effect on cancer risk [50].…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] While the -156G.GG polymorphism of spp1 gene is associated with high cancer risk, the presence of -66T.G SNP may act as a protective factor for human cancers; whereas -443T.C mutation in spp1 promoter is not associated with cancer risk. 46 In case of CRC, mutations in spp1 promoter (rs9138 and rs1126616) were shown to be significant contributors to increased risk of developing CRC. 42,44 Similarly, the presence of spp1 promoter SNPs -443 (rs11730582) and -1748 (rs2728127) was associated with the aggressiveness of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 In fact, SPP1 isoforms mainly SPP1c was associated with worse survival outcomes. [44][45][46][47] While the -156G.GG polymorphism of spp1 gene is associated with high cancer risk, the presence of -66T.G SNP may act as a protective factor for human cancers; whereas -443T.C mutation in spp1 promoter is not associated with cancer risk. 46 In case of CRC, mutations in spp1 promoter (rs9138 and rs1126616) were shown to be significant contributors to increased risk of developing CRC.…”
Section: Discussionmentioning
confidence: 99%